EMPOWERMENT OF EARLY CHILDHOOD EDUCATORS IN PASURUAN REGENCY IN FORMING AN ATTITUDE OF TOLERANCE IN EARLY CHILDHOOD - Syaikhon, Muhammad; Rokhman Saleh, Nanang; Djuwari , Djuwari; Machmudah, Machmudah; Asmara, Berda; Rihlah , Jauharotur (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
One of the major social issues currently faced in Indonesia, particularly in Pasuruan Regency, is intolerance. Educational institutions play a strategic role in instilling values of tolerance to reduce intolerant attitudes, especially from early childhood education. However, early childhood education institutions in Pasuruan Regency face challenges related to educators’ limited understanding of how to foster tolerant attitudes among young children. This community service activity aimed to enhance the knowledge and understanding of early childhood educators regarding the formation of tolerant attitudes in early childhood learners. The program was conducted over four months and involved early childhood educators in Pasuruan Regency, totalling 50 participants. The method employed was educational counseling delivered through lectures and question-and-answer sessions. Participants’ knowledge levels were measured using a pre-test questionnaire prior to the counseling session and a post-test afterward to assess knowledge improvement. The results indicated that only 10 participants (20%) demonstrated adequate knowledge in the pre-test, while post-test results showed a significant increase, with 40 participants (80%) demonstrating improved understanding. In conclusion, educational counseling activities for early childhood educators in Pasuruan Regency effectively increased their knowledge in fostering tolerant attitudes among early childhood learners.